Možnosti mísení pojiv typu PMB RC s pojivem z R-materiálu - Trnka, Lukáš (Vysoké učení technické v Brně. Fakulta stavební, 2021)
Diplomová práce se zabývá možností mísení pojiv typu PMB RC s pojivem z R-materiálu. V teoretické části je uvedena výroba asfaltového pojiva, jeho modifikace a druhy asfaltových pojiv. Je zde vysvětlen princip funkce rejuvenátorů a druhy rejuvenátorů. Dále je zde popsán postup provádění zkoušek na asfaltových pojivech: znovuzískání asfaltového pojiva, penetrace jehlou, bod měknutí (metoda kroužek a kulička), vratná duktilita, bod lámavosti (dle Fraasse) a DSR. V praktické části jsou vyhodnoceny jednotlivé zkoušky a porovnaná jednotlivá asfaltová pojiva

The diploma thesis deals with the possibility of mixing binders of the PMB RC type with a binder made of reclaimed ashalt. lists the types of asphalt binders, its production and modification are in the teoretical part. There is explained the principle of rejuvenators function, types of rejuvenators. The procedures for performing tests on asphalt binders: recovery of asphalt binder, needle penetration, softening point (ring and ball method), reversible ductility, breaking point (according to Fraass) and DSR. Individual tests are evaluated and asphalt mixtures are compared in the practical part of asphalt binder. The diploma thesis deals with the possibility of mixing binders of the PMB RC type with a binder made of reclaimed ashalt. lists the types of asphalt binders, its production and modification are in the teoretical part. There is explained the principle of rejuvenators function, types of rejuvenators. The procedures for performing tests on asphalt binders: recovery of asphalt binder, needle penetration, softening point (ring and ball method), reversible ductility, breaking point (according to Fraass) and DSR. Individual tests are evaluated and asphalt mixtures are compared in the practical part of asphalt binder.
Possibility of mixing PMB RC type binders with reclaimed binder from RAP
Keywords: Asfaltové pojivo; modifikační přísady; R-materiál; rejuvenátor; penetrace jehlou; bod měknutí; vratná duktilita; bod lámavosti; DSR.; Asphalt binder; modifiers; reclaimed asphalt; rejuvenator; needle penetration; softening point; elastic recovery; breaking point; DSR.